2022
DOI: 10.1101/2022.11.20.517251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome editing of an African elite rice variety confers resistance against endemic and emergingXanthomonas oryzaepv.oryzaestrains

Abstract: Bacterial leaf blight (BB) of rice, caused by Xanthomonas oryzae pv. oryzae (Xoo), threatens global food security and the livelihood of small-scale rice producers. Analyses of Xoo collections from Asia, Africa and the Americas demonstrated surprising continental segregation, despite robust global rice trade. Here, we report unprecedented BB outbreaks in Tanzania. The causative strains, unlike endemic Xoo, carry Asian-type TAL effectors targeting the sucrose transporter SWEET11a and suppressing Xa1. Phylogenomi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The international team of scientists sent members in Africa to collect samples of the blight and ran genetic and genomic analyses to determine the causative Xoo strain: “Together, our data showed that representative Tanzanian strains collected in 2019–2021 are phylogenetically related to Asian Xoo strains and have both iTALe and PthXo1 homologs unique to Asian Xoo isolates” (Schepler‐Luu et al , 2023). But the findings created new mysteries as “this outbreak can be ascribed to a recent colonization event by Xoo strains that are most similar to Asian strains, specifically from Yunnan province.” Yunnan Province in southwestern China is famed for its high‐yield hybrid rice and its neatly terraced farming system.…”
Section: No Resistance Against Asian Xoomentioning
confidence: 94%
See 2 more Smart Citations
“…The international team of scientists sent members in Africa to collect samples of the blight and ran genetic and genomic analyses to determine the causative Xoo strain: “Together, our data showed that representative Tanzanian strains collected in 2019–2021 are phylogenetically related to Asian Xoo strains and have both iTALe and PthXo1 homologs unique to Asian Xoo isolates” (Schepler‐Luu et al , 2023). But the findings created new mysteries as “this outbreak can be ascribed to a recent colonization event by Xoo strains that are most similar to Asian strains, specifically from Yunnan province.” Yunnan Province in southwestern China is famed for its high‐yield hybrid rice and its neatly terraced farming system.…”
Section: No Resistance Against Asian Xoomentioning
confidence: 94%
“…Further analysis by the international Healthy Crops team (http://healthycrops.org) that is developing strategies for controlling rice diseases revealed that the plants were afflicted with bacterial blight, a major plant disease caused by the bacterium Xanthomonas oryzae and a special concern for Tanzania, which is dependent on rice to feed its booming population. The coalition of researchers from Africa, Europe, Asia, and North America reported their findings in a preprint (Schepler‐Luu et al , 2023). None of the co‐authors directly involved with Healthy Crops were available for comment.…”
Section: Figure Wilted and Dried Rice Plants Near Dakawa Tanzania Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genome editing is widely used in both model plant and crop species for research and biotechnology (1,2). Combinations of CRISPR/Cas9/Cpf1 and prime editing have successfully generated elite rice varieties with broad-spectrum resistance to bacterial blight and other diseases (3)(4)(5)(6)(7)(8)(9). Major advantages of genome editing over classical breeding include the precision of prime editing, speed, and the ability to target multiple traits simultaneously without linkage drag.…”
Section: Introductionmentioning
confidence: 99%